2016
DOI: 10.1016/j.soildyn.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimum lateral load distribution for seismic design of nonlinear shear-buildings considering soil-structure interaction

Abstract: The lateral load distributions specified by seismic design provisions are primarily based on elastic behaviour of fixed-base structures without considering the effects of soil-structure-interaction (SSI).Consequently, such load patterns may not be suitable for seismic design of non-linear flexible-base structures. In this paper, a practical optimization technique is introduced to obtain optimum seismic design loads for non-linear shear-buildings on soft soils based on the concept of uniform damage distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…[ μ i / μ t ] α where [ V i ] j is the shear strength of the i th floor at j th iteration, μ i is the story ductility ratio of the i th floor, and α is a convergence parameter ranging from 0 to 1 (Step 12). Results of this study and the study carried out by Ganjavi and Hao and Ganjavi et al indicate that this factor is dependent on the design earthquake excitation and dynamic properties of the structure (e.g., fundamental period, damping model, and the level of inelasticity). Based on intensive analyses performed in the present study, it is concluded that for nonlinear systems an acceptable convergence is usually obtained by using α values ranging from 0.02 to 0.08.…”
Section: Analysis Procedures and Optimization Methodology Incorporatinmentioning
confidence: 53%
See 4 more Smart Citations
“…[ μ i / μ t ] α where [ V i ] j is the shear strength of the i th floor at j th iteration, μ i is the story ductility ratio of the i th floor, and α is a convergence parameter ranging from 0 to 1 (Step 12). Results of this study and the study carried out by Ganjavi and Hao and Ganjavi et al indicate that this factor is dependent on the design earthquake excitation and dynamic properties of the structure (e.g., fundamental period, damping model, and the level of inelasticity). Based on intensive analyses performed in the present study, it is concluded that for nonlinear systems an acceptable convergence is usually obtained by using α values ranging from 0.02 to 0.08.…”
Section: Analysis Procedures and Optimization Methodology Incorporatinmentioning
confidence: 53%
“…In this investigation, steel building frames are modeled on the basis of the concept of FEMA‐440 for parametric study, which permits researchers to model special complex building structures as shear‐type buildings, representing multistory buildings having so‐called shear beams or those with relatively stiff diaphragms when compared with columns. In spite of some shortcomings, shear‐building models have been frequently utilized to evaluate the seismic behavior of multistory structures due to their simple forms and low computational efforts enabling a various ranges of parametric studies . In the steel shear‐building structures, beam‐column joints are modeled by bilinear elastic–plastic springs with 3% post‐yield strain hardening as representative of the story lateral stiffness.…”
Section: Building Prototype and Earthquake Ground Motionsmentioning
confidence: 99%
See 3 more Smart Citations